Diagnóstico da gestão e do gerenciamento dos resíduos eletroeletrônicos gerados no campus da Faculdade de Engenharia de Guaratinguetá/Unesp - Camargo, Ingrid Gabrielle do Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Currently, in Brazil, the quantity and quality of new types of wastes, discarded without criteria in urban areas, has been responsible for considerable impacts on public health and the environment. According to a report prepared by the Institute of Applied Economic Research (IPEA), the country loses about U.S. $ 8 billion annually, due lack of waste recycling, which go directly into landfills or dumps. Among these solid wastes are waste electrical and electronic equipment (WEEE), whose characteristics are complex, by having in its composition substances of high value-added and other health hazards which require different treatment of household waste. Aiming to fill the gap in Brazilian environmental legislation, on 02/08/2010, was sanctioned the National Policy Solid Waste (Law No. 12,305), already regulated on 23/12/2010 (Decree No 7404), whose based on the following principles:reduction of waste generation and toxicity of shared responsibility, proper planning management, social inclusion of waste pickers and sustainable production and consumption. Given the above, this work presented here, aims generally present a diagnosis of the current situation of electronic waste generated in the Faculty of Engineering, Campus Guaratinguetá, FEG / UNESP, to provide data for management and management of these waste, based on sustainability, the economic losses and minimizing environmental impacts and public health related to the flow and the improper disposal of these wastes

Atualmente, no Brasil, a quantidade e a qualidade de novos tipos de resíduos, descartados sem critérios no meio urbano, tem se responsabilizado por consideráveis impactos na saúde pública e no meio ambiente. Segundo relatório elaborado pelo Instituto de Pesquisa Econômica Aplicada (IPEA) o país perde cerca de R$ 8 bilhões anualmente, devido falta da reciclagem de resíduos, os quais vão diretamente para aterros ou lixões. Entre estes resíduos sólidos, encontram-se os resíduos de equipamentos eletroeletrônicos (REEE), cujas características são complexas, por terem em sua composição substâncias de alto valor agregado e outras cujas periculosidades requerem tratamentos distintos dos resíduos domiciliares. Visando preencher a lacuna na legislação ambiental brasileira, em 02/08/2010, foi sancionada a Política Nacional de Resíduos Sólidos (Lei n°12.305), já regulamentada, em 23/12/2010 (Decreto n° 7.404), que tem como base os seguintes princípios: redução da geração e nocividade dos resíduos, a responsabilidade compartilhada, planejamento adequado da gestão, inclusão social dos catadores e a produção e consumo sustentáveis. Diante do exposto, este trabalho, que ora se apresenta, tem como objetivo geral, apresentar um diagnostico da situação atual dos resíduos eletroeletrônicos gerados na Faculdade de Engenharia, do Campus de Guaratinguetá, FEG/UNESP, visando fornecer subsídios para a gestão e o gerenciamento desses resíduos, com base na sustentabilidade, nas perdas econômicas e na minimização de impactos ambientais e de saúde pública, relacionados ao fluxo e ao descarte inadequado desses resíduos
Keywords: Resíduos sólidos; Sustentabilidade; Política ambiental; Sustainability